Ultrastructural appearances of a lens with marked polychromatic lustre: evidence for diffraction as a cause. Issue 12 (December 1984) - Hayes, B P; Fisher, R F
Abstract : A human lens showing polychromatic lustre associated with cortical opacities (Christmas tree cataract) has been examined by slit-lamp photography, thin-section light microscopy, and electron microscopy. Anterior epithelial cells were fibroblast-like, and an area of breakdown of cortical lens fibres was observed in the anterior lens, containing feathery fibres, whorls, and process bodies. Parallel sided stacks of fused cell membranes were found beneath the watery area at the same depth as the polychromatic lustre seen in the slit-lamp. The dimensions of these membrane plates are consistent with the diffraction of light by a parallel thin film to give coloured points of light. Deeper areas of small granules between the lens fibres are associated with the main trunk-like opacity and its branches seen with the slit-lamp.